Nâng cao hiệu quả công tác đào tạo cử nhân ngành Quản lí giáo dục Trường Đại học Thủ đô Hà Nội đáp ứng vị trí việc làm tại các cơ sở giáo dục ngoài công lập - Đỗ, Thị Thu Hằng; Nguyễn, Thị Quỳnh (Tạp chí Giáo dục, 2024)
In Vietnam, the demand for the scale and quality of education is increasing, educational administrative positions in non-public educational establishments increasingly require higher knowledge, skills, and competences. Hanoi Metropolitan University has developed and implemented a bachelor’s training program in Educational Management to supplement professional human resources to serve educational activities. This article examines the current status of the competence level of bachelors in Educational Management combined with the current status of the response level of the bachelor’s training program in Educational Management at Hanoi Metropolitan University, from there it proposes 5 measures to improve training quality to meet practical job requirements. The application of measures requires unified and synchronous direction from all levels of management in the school, especially promoting the decisive role of the professional team of lecturers specializing in Educational Management appropriate to the specific implementation conditions of the training process.